Quadrilateral suspensory and straight sesamoidean ligament calcifying desmopathy in an Arabian mare - Hui, S.K.Y.; Turner, S.J.; Leaman, T.R.; de Brot, Simone; Barakzai, S.Z. (Wiley, 2016)
A 5-year-old Arabian mare was referred for the investigation of recent behavioural change, generalised stiffness, and owner-reported polyuria and polydipsia. Clinical examination revealed severe pain associated with palpation along the entire length of the suspensory ligament (SL) and palmar soft tissues of the pastern regions of both forelimbs. Radiographs of the distal forelimbs demonstrated marked radiopaque striations within the straight sesamoidean ligaments (SSL), and less severe but similar changes in the regions of the SL branches. Ultrasonography of both distal forelimbs revealed multifocal, hyperechoic lesions within the SSLs. The SL bodies and branches were enlarged and had mixed echogenicity on ultrasound scan. The horse was euthanased at the owner’s request and submitted for post-mortem examination. Relevant gross findings were restricted to the SLs and SSLs of all four limbs, all of which contained severe mineralisation and irregularly arranged fibres. Histological examination revealed severe, multifocal to coalescing, dystrophic mineralization with cartilaginous and osseous metaplasia, which suggested a primary calcifying desmopathy affecting all four SLs and SSLs. Clinical findings in the case reported here were similar to that of degenerative suspensory ligament desmitis (DSLD) previously reported by many authors, but diagnostic imaging and histopathological findings were significantly different.